2011
DOI: 10.1021/jf104395v
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Temperature-Dependent Changes in Stored UHT Milk

Abstract: Molecular changes in milk proteins during storage of UHT-treated milk have been investigated using two-dimensional electrophoresis (2-DE) coupled to MALDI-TOF mass spectrometry. UHT-treated samples were stored at three different temperatures, 4 °C, 28 °C, and 40 °C, for two months. Three main changes could be observed on 2-DE gels following storage. They were (1) the appearance of diffuse staining regions above the position of the monomeric caseins caused by nondisulfide cross-linking of α and β-caseins; (2) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
70
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 47 publications
11
70
0
Order By: Relevance
“…Additionally, a high molar mass fraction appeared even under reducing conditions after heat treatment at 90 • C for 30 min, which was assigned to a trimer composed of α S1 -, α S2 -, and κ-casein formed as a result of non-disulphide cross-linking. This roughly corresponds to the findings of Holland et al [124] who, however, observed the formation of non-disulphide cross-links between α S1 -, α S2 -, and β-casein during storage of heat treated milk and attributed this to lysinoalanine formation. In the study of Le et al [125], polymer formation during storage of milk protein powders was correlated with the formation of particular Maillard reaction products.…”
Section: Literature Review Of Studies On Cross-linked Caseinsupporting
confidence: 91%
“…Additionally, a high molar mass fraction appeared even under reducing conditions after heat treatment at 90 • C for 30 min, which was assigned to a trimer composed of α S1 -, α S2 -, and κ-casein formed as a result of non-disulphide cross-linking. This roughly corresponds to the findings of Holland et al [124] who, however, observed the formation of non-disulphide cross-links between α S1 -, α S2 -, and β-casein during storage of heat treated milk and attributed this to lysinoalanine formation. In the study of Le et al [125], polymer formation during storage of milk protein powders was correlated with the formation of particular Maillard reaction products.…”
Section: Literature Review Of Studies On Cross-linked Caseinsupporting
confidence: 91%
“…Pinto in a recent work showed that casein lactosylation is a function of the heating intensity [148]. Holland described temperature dependent molecular changes in milk proteins (non-disulfide cross-linking, deamidation and lactosylation) during storage of UHT-treated milk using 2-DE coupled to MALDI-TOF MS [149].…”
Section: Milk Adulterationmentioning
confidence: 99%
“…Production of ultra high temperature (UHT) milk involves heating of milk at a high temperature (usually 130-140 °C) for 3-5 seconds (s) followed by aseptic packaging to produce a 'commercially sterile' product with minimal changes in quality 1 . Thermal treatment enables storage of UHT milk at room temperature up to 9 months, thus, eliminating the requirement for cold chain and refrigeration facilities in the distribution chain.…”
Section: Introductionmentioning
confidence: 99%
“…Maillard products, dehydroalanine and deamidated proteins 1,[7][8][9] . However, the exact sequence and crosslinking mechanisms that lead to build up of sediment or gel is not known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation